Image of Lakulisha on the Lalatabimba of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The lalatabimba (central portion on the door lintel) of the garbhagriha (sanctum sanctorum) doorframe features a seated figure of Lakulisa, while the panel above depicts four-armed male deities, each seated and holding their respective attributes.